2003
DOI: 10.1109/tasc.2003.812399
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical AC susceptibility of superconducting multifilamentary tapes in a perpendicular field

Abstract: We study theoretically the AC susceptibility of hard type-II superconducting multifilamentary tape when placed in a perpendicular AC magnetic field. We focus on three different arrangements of identical filaments of rectangular cross-section: three filaments stacked in the applied field direction (vertical array), three filaments aligned in the field perpendicular direction (horizontal array), and the case of a 3 3 filament matrix. Real and imaginary AC susceptibility are calculated within the critical state f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The frequency dependence of the imaginary part of magnetic susceptibility, which also represents the magnetic ac loss, has been reported in [8][9][10][11][12][13][14][15]. The exact expression that relates magnetic ac loss to the imaginary part of magnetic susceptibility is given in [5,[16][17][18][19]. Analytical studies of the frequency dependence have been reported in [15,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The frequency dependence of the imaginary part of magnetic susceptibility, which also represents the magnetic ac loss, has been reported in [8][9][10][11][12][13][14][15]. The exact expression that relates magnetic ac loss to the imaginary part of magnetic susceptibility is given in [5,[16][17][18][19]. Analytical studies of the frequency dependence have been reported in [15,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this method cannot model the interaction between the PM and the closed HTS ring. [20][21][22][23][24][25][26][27] simulated the interaction between the superconductor and external magnetic field set by boundary conditions.…”
Section: Introductionmentioning
confidence: 99%